DAYA SAING USAHA PARFUM LOKAL AERMI DI ACEH: PENDEKATAN PORTER’S FIVE FORCES - Yulia Annisa; Sathea Vara Larissa; Isna Wahyuna; Nabila Trianingrum; Elza Destira; Aditya Ramadhan (Jurnal Javanica, 2026)
The rapid growth of the domestic fragrance industry has intensified market competition and increased the prevalence of more economical functional substitutes. This study aims to analyze the competitiveness of Aermi, a local perfume brand in Aceh, in maintaining its market position. A descriptive qualitative approach using Porter’s Five Forces framework was employed to map the interaction between external industry pressures and the company’s internal strategic responses. The results indicate that the threat of functional substitutes and the intensity of competitive rivalry pose the greatest pressures on Aermi, driven by consumer price sensitivity during fluctuations in purchasing power. On the upstream side, supplier bargaining power represents a structural vulnerability due to high dependence on imported fragrance essences susceptible to macroeconomic risks. In response, Aermi optimizes its bargaining position through product differentiation (extrait de parfum) and a rapid innovation cycle, launching new variants every 1–2 months to respond to trends among young consumers. Initial financial constraints and high customer acquisition costs are mitigated by leveraging the owner’s social capital. This combination of strategies is expected to enhance competitiveness, reduce consumption switching risk, and support the stability and retention of the reseller network across regions.